Sleep efficiency and duration assessed with metabolic holter: associate with body composition and dietary components: Sleep efficiency and duration - Acar Tek, Nilüfer; Navruz Varlı, Semra; Karaçil Ermumcu, Merve Şeyda; Ertaş Öztürk, Yasemin (Progress in Nutrition, 2020)
Objective: This study was planned to determine the associations between sleep duration, efficiency, quality with dietary components in adults. Methods: This cross-sectional study was conducted with young adults aged between 19-30 years. Sleep duration and efficiency were assessed with Metabolic Holter. Sleep quality was assessed with Pittsburgh Sleep Quality Scale. Three consecutive days’ dietary record was taken at the same time with metabolic holter. Body composition was analyzed with Bioelectric Impedance Analysis. Results: Body fat mass, body fat percent, waist circumference, and waist/hip ratio was found higher in females with poor sleep efficiency, and decreased sleep efficiency correlated with increased waist/hip ratio (r=-0.324; p=0.054). Being female gender and decreased fat mass were shown as major predictors for increased sleep efficiency according to regression analyses. Also, in females with poor sleep quality had higher percentage of body fat mass and body mass index than females with good sleep quality (p<0.05). The body mass index and waist/hip ratio were found higher in males with sleep duration <7 hours. Decreased sleep efficiency correlates with increased body fat mass and the body fat percent in males (p<0.05). Daily dietary protein, tryptophan, polyunsaturated fatty acids and cholesterol intake are significant higher in males who sleep ≥7 hours (p<0.05). Conclusion: Poor sleep efficiency and short sleep duration in males and poor sleep efficiency in females is associated with increased obesity indicators. These associations were found to be partially related by nutrient intakes, especially in males.